ANALISIS SINTAKSIS CAMPUR KODE JEPANG-INGGRIS PADA LIRIK LAGU PUZZLE KARYA AIKA OHNO - Gede Satya Hermawan (Universitas Pendidikan Ganesha, 2014)
In the lyrics of the song Puzzle, note that insertion can only be to the extent of mixing noun. Then, laying constituents in Puzzle songs tend to be placed at the core of the modifier or not at the core explanatory. It is known that the reason for the birth of code mixing in the theme song lyrics Detective Conan Movie is the refashioning against diction. Choice of foreign vocabulary as a constituent in a unit of grammar such as phrases and clauses are considered more attractive and aesthetic.Keywords: code mixing, Jpop, syntactic analysis.